PRiDE Showcase Competition 2023: Fostering Innovation and Entrepreneurship at UiTM, Perak Branch ,Seri Iskandar/ Nor Marini Mohtar - Mohtar, Nor Marini (2023)
6th July 2023 – The Product Idea Innovation (PRiDE) Showcase Competition 2023 is a remarkable event organized by the Malaysian Academy of SME & Entrepreneurship Development (MASMED), in collaboration with the Department of Business and Management, UiTM Perak Branch, Seri Iskandar Campus. This event took place on 6th July 2023 at Dewan Seri Iskandar, gathering students from UiTM, Perak, who are enrolled in the ENT600 course for the March-August 2023 semester.